Copyright Protection Based on Hybrid Image Watermark (DCT) with Audio Watermark (EMD) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
A digital watermark is a type of security that incorporates data into a signal, making it difficult to erase and showing ownership and validity. An important issue brought about by the growing use of the Internet is illicit copyright infringement and authentication. Previous research has proposed several techniques for this problem but has proven them to be either robust, difficult to detect, or fragile and easy to break. Because of this, in this paper, we use two separate kinds of watermarks—one for image and one for audio—to merge these two purposes into one. The image watermark discrete cosine transform (DCT) is renowned for its robustness. It is embedded in an audio watermarking algorithm based on empirical mode decomposition (EMD), ensuring a safe and fragile embedding process. The audio signal was divided into frames, and each one was decomposed by EMD into intrinsic mode functions (IMFs). The DCT watermark bits and the synchronization codes are embedded into the extrema of the first IMF, a high frequency mode sensitive to any small changes in the audio signal. The experimental outcomes suggest that while using two separate kinds of watermarks may seem like a comprehensive solution, it shows the flexibility of EMD and the limits of the DCT watermark technique in different scenarios.